A real-time rule-based expert system for optimising power consumption in a large-scale petrochemical plant - Theron, P. L.(Petrus Lodevicus) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Ing.) -- University of Stellenbosch, 1992.